Inaugural Newsletter of the CGIAR Food Frontiers and Security Science Program - Awinoh, Martha; Hollerich, Gillian; Eriksson, Hampus; Carrillo, Lucia; Taiwo, Ibukun; Andin, Victor; Hanke-Louw, Nora (CGIAR Food Frontiers and Science Program, 2025)
The Food Frontiers and Security Program seeks resilient and inclusive food systems in frontier settings as critical levers for global climate change adaptation and food system transformation. “Frontier” food systems are those situated at the edges of current global research, investment, and innovation priorities geographically and institutionally. We focus on three frontier food systems: (i) fragile and conflict affected systems, (ii) urban and peri-urban environments experiencing urbanization and rapid transformation, and (iii) small island states and territories. All three are characterized by compounded vulnerabilities including institutional fragility, environmental and spatial constraints, production constraints, and exposure to intersecting shocks such as conflict, climate extremes, displacement, and rapid dietary transitions. These characteristics distinguish them from more stable, self-sufficient, and agriculturally dominant ones.